(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Recurrent tonsillitis is a highly incapacitating illness that impacts millions of people throughout the globe. The study "Unveiling the Impact of Age and Immune System on Recurrent Tonsillitis" offers significant findings on the correlation between age, immune system, and recurrent tonsillitis. Through a database search, we found a total of 189 records. Out of these, 127 records were deemed suitable for the investigations. However, only 62 records were actually examined due to duplication or lack of relevance. After conducting a more thorough analysis, we determined that 54 entries should be removed. Out of them, 24 were deemed irrelevant and 27 were identified as duplicates. In addition, three records were eliminated for alternative reasons. After evaluating 66 complete articles to determine their suitability, we incorporated 20 studies into a qualitative analysis and 20 studies into a quantitative analysis without meta-analysis because the studies lacked significant similarity. This systematic review was conducted in accordance with the reporting criteria of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The results of our study demonstrate a notable association between age and impaired immune system performance in individuals with recurrent tonsillitis. The risk of bias assessment revealed methodological issues in current studies, underscoring the necessity for rigorous research. Our thorough investigation offers a structure for comprehending the intricate relationship between age, the immune system, and recurring tonsillitis. This study serves as a clarion call for future studies to overcome the methodological inadequacies and understand the riddles behind this ailment, opening the way for innovative treatments.